Rheumatic disorders in primary biliary cirrhosis. Issue 1 (February 1978) - Clarke, A K; Galbraith, R M; Hamilton, E B; Williams, R
Abstract : Eighty-three patients with primary biliary cirrhosis were investigated to determine the prevalence of rheumatic disorders. 14 had scleroderma, which tended to be mild but in several patients produced severe systemic manifestations. The CRST syndrome (calcinosis, Raynaud's phenomenon, sclerodactyly, telangiectasia) was only identified twice. There was an increased incidence of HLA A1+B8 in those patients with scleroderma. As well as those with scleroderma, 4 patients had a destructive arthropathy resembling avascular necrosis. 4 patients had an inflammatory arthritis, without specific features, but the frequency was no greater than might be expected in the general population.